Biomechanics—Hot Topics Part II. (March 2018) - Finkemeier, Christopher; Adams, John D.; Bernstein, Mitchell; Lee, Mark A.; Harvey, Ed; Crist, Brett D.
Abstract : Summary: Orthopaedic surgery and biomechanics are intimately partnered topics in medicine. Biomechanical principles are used to design implants and fashion treatment protocols. Although it would seem that biomechanical principles in the design of fixation devices and fracture repair constructs have been already finalized, there are several points of controversy remaining. New technology has raised new questions, while at the same time, we still do not fully understand simple clinical principles such as time of fracture healing depending on the construct used. This review looks at several of these current controversies to better understand what work is needed in fracture care going forward.